Peranan Komunikasi Interpersonal Dalam Manajemen Konflik Keluarga - Vicania, Iit; Naqiyah, Najlatun; Purwoko, Budi; Habsy, Bakhrudin All (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2024)
Differences are the nature of every human being. Conflicts in the family arise because of differences between husband and wife that are ignored and not managed and resolved properly. If a conflict is not managed well, it can result in domestic violence and lead to divorce. This article describes the role of interpersonal communication in managing family conflict, discussing how interpersonal communication strategies can be used in an effort to manage conflict management in the family. Discusses strategies that can be used in managing family conflict. This article aims to provide a contribution of thought in building a household, a spiritual and physical bond between husband and wife as capital for creating a household and the realization of a sakinah family, mawadah wa rahmah, namely a happy family and the approval of Allah SWT